(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2025)
The effect of cylinder orientation on the free convective heat transfer in glycerol is studied for the Rayleigh numbers, 10-6 ≤ Ra ≤ 109 and Prandtl number, Pr = 11630. While varying the orientation of the cylinder, correlations due to Churchill & Chu, Raithby & Holland, Kuehn & Goldstein, Fand et al, Jaluria and Neeta et al are used to evaluate the free convective Nusselt number as a function of Rayleigh number at orientations of 00, 100, 200, 300, 400, 500, 600, 700, 800 and 900. Additionally, the Rayleigh number is kept fixed at three regimes of 10-6, 100 and 106 and the free Nusselt number is evaluated as a function of the cylinder orientation. At maximum orientation (θ = 900) an increase of 114% in Nusselt number is observed for Kuehn & Goldstein correlation